Relationship Organization and Price Delegation: An Experimental Study - Lim, Noah; Ham, Sung H. (Management Science, 2014)
Price delegation to the salesforce is a practice widely adopted by firms. This paper examines the relationship between price delegation and managerial profits using a laboratory economics experiment. A novel feature of our experiment is that we study how varying the relationship organization of the sales manager and salesperson to allow for (1) requests by the salesperson for the manager to choose price delegation, and for (2) the manager to award a small bonus after observing the salesperson's decisions, can affect behavior. The results show that, contrary to the theoretical prediction, managers choose price delegation frequently and salespeople respond reciprocally, leading to higher manager profits under price delegation. Moreover, this behavior increases when requests and bonuses are allowed. We show that a behavioral economics model that incorporates positive reciprocity can explain these results well. Data, as supplemental material, are available at http://dx.doi.org/10.1287/mnsc.2013.1778 . This paper was accepted by Pradeep Chintagunta, marketing.